The appropriate criminalisation for the petrol used in drug trafficking - Arcas Ruiz, Víctor Manuel (Logos Guardia Civil, Scientific Magazine of the University Center of the Guardia Civil, 2025)
The present work deals with the illegal supply of fuel, “gasoline”, intended to be used in high-speed rigid inflatable boats. These boats have been commonly referred to as "narco-boats" in both law enforcement and journalism contexts. This gasoline, known as "narco-gasoline," is a vital part of the logistical operations involved in the trafficking of hashish from North Africa. Additionally, it poses a series of risks and dangers, particularly those affecting important legal assets such as human life, the natural habitat, and consequently, the environment. The study examines whether Spanish substantive law “criminal code” has the necessary capacity and structure to serve as an adequate legal tool that enable prosecutors, judges, and law enforcement services to combat the phenomenon of "narco-gasoline, “or it is the opposite and our penal law requires to be amended by the legislative authorities in order to repress this dangerous and illicit conduct.